Upaya Meningkatkan Membaca Permulaan Melalui Metode Struktur Analisis Sintesis Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas I SD Negeri 26 Kota Ternate - Iwan Irawan; Nurfia Abdullah; Riyani Basir (Peneliti.net, 2022)
This study aims to improve Premulaan Reading Ability through synthesis analysis structure methods in the subject of Indonesian Shiva Class I SD Negeri 26 Ternate City for the 2019/2020 School Year. This study is a Class Action Research (PTK) of the research subjects of grade I students totaling 20 male students 11 and 9 women. Research procedures: (1) planning, (2) action or action (acting), (3) observation (observationing), (4) reflection (reflecting). data and data sources in the form of information about the learning process Indonesian with the Synthesis Analysis Structure method and the ability to read the beginnings obtained from the results of the cycle I test, and the CYCLE II test. Indicators of the initial reading ability of students passed the KKM (65) from the number of all students (20 students). The results of this study show that the learning process regarding the ability to read the beginning using the Synthesis Analysis Structure method makes grade I students of SD Negeri 26 Ternate City become more active, so that learning becomes more effective. In addition, it can improve the ability to read the beginning in bajasa Indonesia subjects, this can be proven by the increase in learning in the first cycle of students who are categorized either only 8 students or (40%0 while the low category is 5 students or (25%) and the lace category once there are 7 students or (35%). In cycle II, students experienced an increase in the number of reading completions at the beginning of grade I students in cycle II and reached the set indicator of 100%. the average score of students learning the Synthesis Analysis Structure method in cycle I was 5.65% while cycle II was 8.27%.